2022
DOI: 10.3390/d14010034
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination and Seedling Growth of Robinia pseudoacacia Depending on the Origin of Different Geographic Provenances

Abstract: Black locust (Robinia pseudoacacia) is recognised as a forest species of interest due to its multiple uses. The management of forest genetic resources and their efficient conservation suffer from variations in traits and start with seed germination. The aim of the current study was to investigate the germination of seeds obtained from plus trees selected in eight Romanian provenances, as well as to investigate the influence of the origin upon plants’ growth and development. Two experiments were undertaken to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Morphological traits noted for black locust seeds indicated that the origin was relevant for the current investigation, with the data being quite variable [6]. The present study revealed seed traits such as thickness, length, width, and weight, which are represented as a boxplot diagram (Figure 2) consisting of the minimum and maximum range values, the upper and lower quartiles, as well as the median, to summarize the distribution of the dataset recorded.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Morphological traits noted for black locust seeds indicated that the origin was relevant for the current investigation, with the data being quite variable [6]. The present study revealed seed traits such as thickness, length, width, and weight, which are represented as a boxplot diagram (Figure 2) consisting of the minimum and maximum range values, the upper and lower quartiles, as well as the median, to summarize the distribution of the dataset recorded.…”
Section: Discussionmentioning
confidence: 66%
“…The first treatment referred to the mechanical scarification method, using abrasive sandpaper until the tegument was visibly damaged [17]. The second type of treatment (thermal treatment) involved water-soaked seeds at different temperatures [3,6]; seeds were soaked for 10 min in water at a temperature of 100 • C, 70 • C, and 40 • C. For the third treatment, seeds were soaked in biostimulator solution (Foliplant, 0.9%) for 10 min [21]. The fourth treatment used acetone (90%) solution for 10 min of seed imbibition [22].…”
Section: Germination Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Difference in germination rate and germination timing under various conditions has a significant impact on recruitment and potential competitive ability of seedlings [16,17], which then determines population distribution and community structure [18]. A great number of studies have demonstrated the effects of environmental factors (e.g., temperature, light, soil moisture and salinity) on seed germination [19][20][21][22], but few considered the biotic interactions among seeds. In field sites, seeds of different species often appear in the same place due to the dispersal by wind, tide or animals [23,24], which makes the germination process affected by neighbouring conspecific or heterospecific seeds.…”
Section: Introductionmentioning
confidence: 99%